2015
DOI: 10.1371/journal.pone.0124533
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Reported Clinical Practice Behaviors of Australian Optometrists as Related to Smoking, Diet and Nutritional Supplementation

Abstract: ObjectiveThe primary aim of this study was to examine the self-reported, routine clinical practice behaviors of Australian optometrists with respect to advice regarding smoking, diet and nutritional supplementation. The study also sought to assess the potential influence of practitioner age, gender, practice location (major city versus regional), therapeutic-endorsement status and personal nutritional supplementation habits upon management practices in these areas.MethodsA survey was electronically distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 46 publications
8
62
0
Order By: Relevance
“…These findings suggest that optometrists prefer pre‐appraised and synthesised evidence, over independently accessing primary sources and undertaking their own appraisal and interpretation of research studies. These preferences mirror those reported for other areas of optometric practice, including dry eye disease and age‐related macular degeneration …”
Section: Discussionsupporting
confidence: 70%
“…These findings suggest that optometrists prefer pre‐appraised and synthesised evidence, over independently accessing primary sources and undertaking their own appraisal and interpretation of research studies. These preferences mirror those reported for other areas of optometric practice, including dry eye disease and age‐related macular degeneration …”
Section: Discussionsupporting
confidence: 70%
“…Smoking cessation is a complex issue. Primary eye care clinicians indicate that the care they provide to patients in relation to advice to quit smoking is influenced by multiple factors; it can be limited by consultation time constraints, a perception of sufficient public awareness about the health risks and/or the view that questioning patients about smoking behaviour is relatively awkward and intrusive . Similar perceived barriers were described in a study that surveyed ophthalmologists and optometrists practicing in the United States .…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies that have surveyed primary eye care clinicians practicing in various regions of the world, highlight similar deficiencies in care provision in this practice area. Our recent research, which evaluated the self‐reported routine practices of Australian optometrists, suggests that less than half of practitioners routinely enquire about their patient's smoking behaviours . Corroborating this finding are the data in the present survey, in which about only about one‐third of patients indicated that their optometrist had asked them about their smoking behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations